A Novel Technique Using Customized Headgear for Fixation of Rigid External Distraction Device in an Infant With Crouzon Syndrome. Issue 8 (November 2015) - Hariri, Firdaus; Rahman, Zainal Ariff Abdul; Mahdah, Saridah; Mathaneswaran, Vickneswaran; Ganesan, Dharmendra
Abstract : Abstract: Rigid external distraction device is often indicated for superior midfacial advancement in pediatric syndromic craniosynostosis patients. Even though the technique is proven reliable to treat the functional issues related to the craniofacial deformity, major complications associated with its fixation, such as intracranial pin perforation and migration have been reported. We report a novel technique of using a customized headgear to prevent intracranial pin perforation over a very thin temporal bone region in an 8-month-old infant with Crouzon syndrome who underwent monobloc Le Fort III distraction osteogenesis using a combination of bilateral internal and a rigid external distraction device. The customized headgear provides a protective platform at the temporal region thus preventing intracranial pin perforation and allows stable fixation during the early phase of consolidation period to prevent central component relapse. The headgear can be used short term when rigid external distractor is indicated in infant patient but requires close monitoring because of risks of skin necrosis and temporal region indentation.